Analisis Faktor-Faktor Yang Mempengaruhi KualitasHasil Audit Di Lingkungan Pemerintah Daerah(Studi Kasus Pada Inspektorat Pemerintah Kota Surakartadan Kabupaten Boyolali) - Nurul Laili, Fatihah, Drs. Wahyono, M.A, Akt, CA (2017)
The purpose of this research was to examine the effect of the independency, objectivity, integrity, competence and ethics audit to quality of audit result in the Inspectorate of Surakarta and Boyolali. The population in this research are all government officers who work in the Inspectorate of Surakarta and Boyolali. Sampling was conducted using a purposive sampling method and number of samples of 48 respondents. The data in this research is obtained by distributing questionnaires to the respondents. Data analysis used in this research is mutliple liniear regression analysis. The results of this research showed that the variables of independency, objectivity, integrity, competence and ethics audit have influence on quality of audit result.